Investigation of factors affecting development of browning during Maillard reaction of gelatin - Hammed, Ademola Monsur; Hamzah, Anis; Asiyanbi-H, Tawakalit Tope; Mirghani, Mohamed Elwathig Saeed; Jaswir, Irwandi; Ahmad Fadzillah, Nurrulhidayah; , (2017)
The development of browning of gelatin and hydrolyzate is affected by the reaction conditions of during xylose-induced Maillard reaction. Change in browning index increases with degradation of enzyme, concentration of xylose, presence of Cu and Fe ions and increase in type of reaction. However, increase in concentration of Cu ion above 2.5mM lack significant effect on change in browning index of gelatin hydrolysate. The discrimination of gelatin is achievable in the first 6 hr of reaction time. There was high increase in browning index of fish hydrolyzate compared to that of mammalian source. This approach will found useful for development of rapid and cheap UV-spectroscopic method for Halal authentication. Contribution: We have investigated the use of UV-spectroscopy for development of protocol for specie specific gelatin authentication for halal industrial. The transformation of gelatin during xylose-induced browning reaction was adequately described using change in browning index.